(untitled) (Raparin Journal of Humanities (RJH), 2023)
This research is entitled "Philosophical Pessimism in Contemporary Kurdish Poetry with the Example of the Poems of (Jamal Ghambar, Barzan Hastyar, Abdullah Pashew)". The paper discusses philosophical pessimism as a multidimensional subject in modern Kurdish poetry and the root of pessimism in Kurdish and other languages. Specific concepts and themes of pessimistic philosophy such as nihilism, death-loving and doubt have also been theorized and practiced. Finally, we have reached several conclusions that philosophical pessimism in contemporary Kurdish poetry is a pessimism that has emerged under the influence of a number of literary movements such as Surrealism, Absurdism, Dadaism and Nihilism. However, philosophical pessimism in Kurdish poetry is more of an intellectual than an ideological issue for most poets.